Innovation Adoption Process Using the Online Anywhere Service Application at the Population and Civil Registration Office of Tanah Datar Regency - Riska Rahmadani; Zulkarnaini Zulkarnaini (CV. Rayyan Dwi Bharata, 2023)
Innovation renewal is present as an effort to use technology to optimize service to the community. One form is in the form of online services for various community affairs by government institutions. This research was conducted to find out how the process of adopting online service innovations via the Online Anywhere Service (OASE) application at the Population and Civil Registration Office of Tanah Datar Regency was carried out by the Population and Civil Registration Office (Disdukcapil) of Tanah Datar Regency using Rogers' Theory. This study uses a descriptive qualitative approach. Data were collected using field research techniques, including observation and in-depth interviews with purposive sampling techniques to determine informants. The results of this study are that online services via the OASE application for the Population and Civil Registration Office of Tanah Datar Regency were successfully adopted from the knowledge stage to the confirmation stage, because the informants considered them to be according to needs and more flexible. Pamphlets and banners are communication channels that act as initial information dissemination tools. It is also known that interpersonal communication between the community and government representatives acts as a process of exchanging information for adopters to obtain additional information. Informants' ability to use technology influences their perceptions in seeing the degree of relative advantage, suitability, and complexity of the innovation.